Effects of thrombocytopenia in pregnancy - Kapadia, Shital N.; Patel, Harsh S.; Parmar, Kartikey G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Thrombocytopenia defined as platelet count of less than 1,50,000/cu.mm. Thrombocytopenia is divided according to severity into mild moderate and severe types. Multiple factors are responsible. Methods: This is a retrospective study of one-year period including 120 pregnant patients irrespective of their gestational age at civil hospital Ahmedabad. Etiology of this condition are identified and analyzed. Results: Gestational Thrombocytopenia is the most common etiology. This condition is self-limiting usually. Conclusions: Platelet count estimation should be a routine at first antenatal visit for timely diagnosis and to achieve favorable fetomaternal outcome.